Manufacturing of beach cleaning machine at Universiti Malaysia Sabah (UMS) prototype design and analysis - Nurmin Bolong; Ismail Saad; Mohd Amran Madlan (e-VIBS, Faculty of Science and Natural Resources, 2021)
A beach cleaning machine that suits local Kota Kinabalu shoreline beach profiles is designed and developed in this paper. For a clean future, beach cleaning is essential to collect garbage from the beach with a simple and practical design and at the same time able to create an environmentally user-friendly influence. This work has developed a custom-made beach cleaner machine by incorporating local fabricator and mechanical equipment such as collector, conveyor, motor, and gears by applying walk-behind sifting-raking systems for a single man. The UMS-Beach Cleaning Machine (UMS-BCM) operation and implementation were studied at UMS Outdoor Development Centre (ODEC) beach, part of Teluk Likas beach at Kota Kinabalu, Sabah. The methodology involves operation and specification analysis of the prototype, testing on-site, and user surveys. Up to 88% of the users agree that the application of the UMS-BCM can ease and help clean the beach, and most of them (94%) giving positive feedback where they can operate the device efficiently as a single operator.